Changes in Latin American agricultural markets - Reca, Lucio G.; Díaz-Bonilla, Eugenio (International Food Policy Research Institute, 1997)
This paper presents an overview of macroeconomic and agricultural trends in Latin America and the Caribbean. It argues that world-level macroeconomic and agricultural cycles, of expansion during the 1960s and 1970s, and stagnation and retrenchment during the 1980's, had an important impact on the economies of the LAC countries and on the performance of the agricultural sector in the region. They played over, and interacted with, a sustained trend of technological change in agriculture, that had begun in the developed countries before, and that in the last quarter of a century spread to developing countries.